2014
DOI: 10.2147/opth.s30278
|View full text |Cite
|
Sign up to set email alerts
|

Critical appraisal of loteprednol ointment, gel, and suspension in the treatment of postoperative inflammation and pain following ocular and corneal transplant surgery

Abstract: PurposeTo review comprehensively the available peer-reviewed published articles in the literature on loteprednol suspension, gel, and ointment in the treatment of ocular inflammation and pain following ocular surgery.MethodsWe conducted a PubMed literature search review of all published articles on keywords associated with loteprednol etabonate and ocular surgery.ResultsA total of 59 peer-reviewed articles were found in the literature. The focus of the majority of the articles was on the safety and efficacy of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Of 1863 systematic reviews on eyes and vision in our database as of March 2016, we identified 99 that evaluated management strategies for cataract in the adult eye and were eligible for this project (Figure 1). The earliest review was published in 1994, but more than half were published after 2012 (Table 2). Twenty of 99 reviews (20%) were published by CEV authors in The Cochrane Database of Systematic Reviews .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of 1863 systematic reviews on eyes and vision in our database as of March 2016, we identified 99 that evaluated management strategies for cataract in the adult eye and were eligible for this project (Figure 1). The earliest review was published in 1994, but more than half were published after 2012 (Table 2). Twenty of 99 reviews (20%) were published by CEV authors in The Cochrane Database of Systematic Reviews .…”
Section: Resultsmentioning
confidence: 99%
“…Twenty of 99 reviews (20%) were published by CEV authors in The Cochrane Database of Systematic Reviews . Of the 79 non-Cochrane reviews, 50 (63%) were published in specialty medical journals (eg, Ophthalmology ). Intraocular lenses (IOL) implantation was the most commonly examined intervention (25 of 99 [25%]), followed by phacoemulsification (20 of 99 [20%]).…”
Section: Resultsmentioning
confidence: 99%
“…A preservative-free LE ointment 0.5% formulation became available in 2011. Ointment formulations may be beneficial for patients with tremors or arthritis as well as others who may have trouble instilling drops into their eyes [53], and remain on the ocular surface significantly longer than ophthalmic solutions, making them particularly suitable for nighttime use [54].…”
Section: Le Ointmentmentioning
confidence: 99%
“…The increased surface area of these junction areas leads to improved tensile strength of the wound, allowing for earlier sutures removal and potentially reducing graft rejection [12]. Then patients can also be safely switched to less potent topical steroid medications which are known to have fewer long-term side effects for chronic maintenance of immune-suppressive therapy [13].…”
Section: Discussionmentioning
confidence: 99%